Socio-Economic Status of Tribal Backyard Poultry Rearers in Bastar District of Chhattisgarh - A.K. Chaturvedani , Niranjan Lal , Jitendra Pratap and N.K. Khyalia, (Indian Journal of Extension Education, 2017)
The present study was conducted in the Bastar district of Chhattisgarh with the specific objective of finding outthe socio-economic profile of the backyard poultry rearers. A multi-stage random sampling procedure was used toselect 120 respondents (12 respondents per village) for the study. A structured interview schedule duly pre-testedand validated was used to elicit information from the respondents. The findings of the study revealed that most ofthe poultry rearers (58.00%) were middle aged belonged to Gond tribe (55.83%) with primary to secondary leveleducation and small size family, agriculture as primary (51.67%) and poultry as secondary occupation (35.38%),with medium flock size (11-16 birds) poultry farms. Majority (84.17%) of the respondents were marginal to small landholding and getting low level of income (67.50%). Majority (51.67%) of the respondents had low level of materialpossession. The study concludes that the backyard poultry production needs more extension training to enrichtheir skill and to improve their standard of living.